Faktor - Faktor Yang Mempengaruhi Impulse Buying Pada Masyarakat Desa Sebewe Dalam Penggunaan Aplikasi Shopee - Hanifa Sri Nuryani (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of the study was to examine the effect of Shopping Lifestyle, Fashion Involvement, Hedonic Shopping Motivation on the Sebewe Village Moyo Utara District Community Users of the Shopee Application. The sampling technique used is Purposive Sampling. The research sample is the Sebewe Village Moyo Utara District Community using the Shopee application. The analytical tool used in this research is Multiple Linear Regression. The results of this study indicate that Shopping Lifestyle has a positive and significant effect on Impulse Buying, Fashion Involvement has a positive and significant effect on Impulse Buying, Hedonic Shopping Motivation has a positive and significant effect on Impulse Buying